MicroRNA function is required for neurite outgrowth of mature neurons in the mouse postnatal cerebral cortex - Hong, Janet; Zhang, Haijun; Kawase-Koga, Yoko; Sun, Tao (Frontiers in Cellular Neuroscience, 2013)
The structure of the postnatal mammalian cerebral cortex is an assembly of numerous mature neurons that exhibit proper neurite outgrowth and axonal and dendritic morphology. While many protein coding genes are shown to be involved in neuronal maturation, the role of microRNAs (miRNAs) in this process is also becoming evident. We here report that blocking miRNA biogenesis in differentiated neurons results in microcephaly like phenotypes in the postnatal mouse brain. The smaller brain defect is not caused by defective neurogenesis, altered neuronal migration or significant neuronal cell death. Surprisingly, a dramatic increase in neuronal packing density within the postnatal brain is observed. Loss of miRNA function causes shorter neurite outgrowth and smaller soma size of mature neurons in vitro. Our results reveal the impact of miRNAs on normal development of neuronal morphology and brain function. Because neurite outgrowth is critical for neuroregeneration, our studies further highlight the importance of miRNAs in the treatment of neurological diseases.